2015
DOI: 10.1016/j.ajog.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous oxytocin modulates human myometrial microRNAs

Abstract: Oxytocin alters the expression of a unique set of myometrial miRNAs. These results suggest a further role for oxytocin as a signaling molecule that is involved in the regulation of gene expression during parturition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…8 MiR-873-5p has been reported to be an endocrine related miRNA that can be regulated by exogenous oxytocin in human myometrium. 18 In the present study, we found that miR-873-5p levels were signicantly up-regulated in follicular uid from patients with PCOS. It has been revealed that the oxidative stress level is signicantly increased in PCOS patients compared with normal individual.…”
Section: Discussionsupporting
confidence: 50%
“…8 MiR-873-5p has been reported to be an endocrine related miRNA that can be regulated by exogenous oxytocin in human myometrium. 18 In the present study, we found that miR-873-5p levels were signicantly up-regulated in follicular uid from patients with PCOS. It has been revealed that the oxidative stress level is signicantly increased in PCOS patients compared with normal individual.…”
Section: Discussionsupporting
confidence: 50%
“…A recent study in human myometrium has identified a miRNA 'fingerprint' in term labouring samples that is different to those following exogenous oxytocin administration [60]. This illustrated a unique profile different to that observed in samples from spontaneous labour.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This illustrated a unique profile different to that observed in samples from spontaneous labour. Activation of OTR via exogenous OT administration contributes to the onset of labour by regulating the expression of miRNAs, hsa-miR-146a-5p, -196a-3p, -876-5p, and -146b-3p [60]. While further work is required to define the exact biological significance of these changes, in silico miRTarBase platform analysis…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Previous studies concerning miR-873-5p function have been quite broad, from cancers [156][157][158][159] to immunity [160,161], and pregnancy [162][163][164]. However, the overall pattern of enrichment of the miR-873-5p WT pulldown experiment measured with GSEA suggested an association with potassium channel signalling (Supplemtary Table 4.3), which has not been previously suggested.…”
Section: Discussionmentioning
confidence: 76%
“…MicroRNA miR-873 is located within the neuronally expressed LINGO2 gene, nearby another mi-croRNA, miR-876, and the three genes have correlated expression [155]. MiR-873 has been studied or found dysregulated in a number of diverse contexts, including cancers [156][157][158][159], immune system [160,161], and pregnancy [162][163][164]. There is also evidence for a neuronal function, as a heterozygous deletion of this region has been observed in an individual with craniofacial abnormalities and learning difficulties [155].…”
Section: Introductionmentioning
confidence: 99%